The influence of self-organized education according to the pintrich classification in learning to swim freestyle for students (Journal of the College of Basic Education, 2025)
The research aims to : Preparation of educational modules using self-organized education according to the pintrich classification)) fit the capabilities of the research sample. Identify the effect of self-organized education according to the pintrich classification in learning to freestyle for a research sample. Research hypothesis: The presence of significant differences between the results of the dimensional tests of the control and experimental groups in learning the skill of freestyle swimming. Research areas: Human field: first-stage students at the Faculty of physical education and sports sciences, Qadisiyah University, numbering (40) students. Time domain: duration: 8/10/2024 to 18/2/2025. Spatial field: the educational pool of physical education and Sports Sciences of the University of Qadisiya. The researcher used the experimental method on two groups and designed the equal control and experimental groups, which are the students of the first stage at the Faculty of physical education and sports sciences, Qadisiyah University, numbering (340) students, and he took (5) students from them in order to conduct the exploratory experiment, so the research sample amounted to (40) players, and their percentage was (11.7).% ) Of the indigenous community. The curriculum took (8) weeks and actually one educational unit per week. After the completion of the curriculum, dimensional tests were conducted and appropriate statistical treatments were used, and the researcher reached the conclusions that the exercises of educational modules self-organized education according to the pintrich classification have a positive effect in learning swimming sports and the researcher recommends that educational modules self-organized education according to the pintrich classification can be used in small and specific spaces and areas, especially if.